Rekayasa Material Serat Alternatif Melalui Desain Mesin Pengurai Sabut Kelapa - Nanang Endriatno (Program Pendidikan Vokasi Teknik Mesin, 2025)
Coconut fiber is a byproduct of the coconut industry that is abundant and has not been utilized optimally. Coconut fiber has good mechanical properties, is environmentally friendly, and has the potential to be used as an alternative fiber material. This study aims to design a coconut fiber decomposing machine that is capable of producing alternative fiber materials. The research methods include literature study, machine mechanism design, and machine design. The machine is designed with a 30x30x3 mm angle profile steel frame measuring 700x500x400 mm in height x length x width, using a decomposing cylinder with a diameter of 164 mm and a length of 355 mm. The decomposing cylinder functions to decompose coconut fiber into fiber. Another main component is the coconut fiber holder plate that functions to clamp the coconut fiber to keep it in position during machine operation. The coconut fiber will be held in the coconut fiber holder, while the other part will fall through the outlet channel. This machine is driven by a 5.5 HP electric motor with a maximum rotation of 1400 rpm. The transmission system uses a belt and pulleys, with a 70 mm input pulley and a 200 mm output pulley, producing a maximum rotation speed of 490 rpm. The design is expected to make a machine capable of increasing the added value of coconut fiber waste and supporting the development of alternative fibers based on natural fibers.